The Lesson Learned from the Waste Management Project along with Sustainable Environmental Development into a Natural Classroom “Bavorn” - Nantasang , Alongkorn; Sripokangkul, Siwach (Journal of Modern Learning Development, 2023)
The Waste Management and Sustainable Environment Development (called, in short, "Bavorn") had the objectives to study the implementation of the project on waste management and sustainable environmental development in a natural classroom setting ("Bavorn"). The research examined the implementation before and after receiving the first prize in the community category of Kham Si Community and Si That Subdistrict Municipality, Si That District, Udon Thani Province. The research explored oobstacles to the operation and factors that affected the success of the project. Data were collected by in-depth interviews with key informants from the following: (1) Community Department, 10 persons; 2) Local Administrative Organization, 10 persons. The study found that the project implementation involved participation from all the relevant sectors and consisting of the following seven core activities: 1. Activities to reduce downstream waste by using local packaging; 2. Mobilizing donations for monks’ robes to contribute to the construction of a chedi at Wat Si Sawang Boromsuk in the name of waste management; 3. Planting saplings using empty school milk cartons; 4. Household composting activities from discarded food and leaf scraps from households; 5. Vegetable gardening activities for cooking and exchanging produce within the community; 6. Activities to increase green areas in the vacant areas of ​​Sri That Kindergarten, public parks and communities; and 7. Activities to reduce electricity consumption of network partners in the community. This study also identifies the following obstacles to successful implementation: 1. Lack of continuity of project operations; 2. Illegal forest encroachment; 3. Unconstructive attitudes by some members of the community; 4. Inability to produce an adequate supply of sticky rice containers; 5. Lack of community knowledge in organic waste management; and 6. Improper management of wastewater in households, restaurants, slaughterhouses, and fresh markets. The factors that promoted success of the project include the following: 1. Good resource management; 2. Participatory operations in the “Bavorn” style, i.e., representatives of the host communities, temples, and schools actively joined in project activities; 3. Executives focused on project operations and recognized the importance of the mission, including provincial executives, the chief district officer, municipal administrators, village headmen, and temple abbots; 4. The project interventions are replicable and help to create a database; 5. The project personnel have knowledge and ability to connect with network partners; and 6. Representatives of the relevant agencies gave importance to the project.